Design and Evaluation of Educational Socio-environmental Games to Identify Attitudes, Motivations and Decisions of Smallholder Contemporary Rural Youth - Meza-Jiménez, Amayrani; García-Barrios, Luis Enrique; Saldívar-Moreno, Antonio; Vera-Noriega, José Ángel (Revista Electrónica Educare, 2016)
The current and potential relationship of contemporary rural youth with the agricultural and natural patrimony (PAN, according to its Spanish initials) that they will inherit is little known, but vitally important. In this study, we designed, adapted, and evaluated a variety of socio-environmental learning tools in order to identify and reflect on the opinions, actions, and motivations of 14 to 17 year olds in an area of the Sepultura Biosphere Reserve in Chiapas, Mexico to use their PAN in the future. The methodological approach consisted of exploring discourses using the Q method and three original table games (Mi territorio ideal, El carga palito y Manantiales de la Sierra). 46 teens were shown how to use these four tools, their use was monitored in workshops, and results were recorded and statistically analyzed. These tools allowed a) identifying at least four discourses of the teens regarding the use of their PAN, and b) reveal to the teens the preferences for land use, levels of diversification and intensification, and their disposition toward behaviors of dominance/subordination, competition, cooperation, coordination, equity, and solidarity that emerge from their decision making regarding PAN. Participants said they understood and enjoyed these tools, and that they learned about their own motivations. Together, these materials conform a dynamic educational approach that allows teachers and students to identify external and internal motivations, conservation behavior, intensification and diversification for managing PAN, attitudes of dominance and equity among teens, and preferences towards individual or collective working. This proposal is innovative, participatory, dynamic, and contextualized, and has great potential to be incorporated in the middle school curriculum in the study area and in similar rural regions of Mexico, as well as in the rest of Latin America and the world.